ETR-AR: Augmented Reality Intervention in A Web-Based Card Game of The Emerging Technology Revolution Concepts - Ong , Sin Nee; Nordin, Noradila (Multidisciplinary Applied Research and Innovation, 2021)
In this new era of remote learning, technology knowledge is vital as it provides endless possibilities of using various technologies to be incorporated into the teaching and learning processes. One of the technologies is augmented reality (AR). AR is an overlay of computer-generated information on the real world in real-time. By integrating AR, it helps to improve the students' knowledge retention as the interactive content is more attractive than the typical static content. This project proposed ETR-AR, a web-based card game with AR intervention to assist learners in overcoming the problems in understanding the concepts of the emerging technology revolution in the Computer Application in Management curriculum offered in Universiti Utara Malaysia, Malaysia. ETR-AR consists of two main parts which are the web interface and card-based AR with 3D, developed using HTML, PHP, JavaScript, and CSS, and A-Frame and Augmented Reality JavaScript (AR.js). ETR-AR was evaluated by 32 undergraduate students enrolled in the course. It was found that 93.75% of respondents agreed that the web application can increase their knowledge of the concepts and 96.88% found that the AR elements of the cards attracted them. Based on tests that were conducted on the respondents, 37.5% showed an improvement in their marks after using ETR-AR as a revision method. ETR-AR can attract learners through its additional element of AR and gamification.